The Application of a Cost Plus Pricing Method in Determining the Selling Price of Dried Lomek Products (Case Study at Bumdes Kuala Alam) - Siti Nurhaliza; Wan Junita Raflah (Politeknik Negeri Bengkalis, 2022)
The determination of the selling price will affect the level of consumer purchasing power, specifically, if the price offered is too high, it will have an impact on the decline in consumer purchasing power. As a result, the product willbe unable to compete in the market and vice versa. Even though the products offered at low prices can compete in the market, the profit achieved by the company will not be maximized. This study aims to determine the selling price of dried lomek products at BUMDes Kuala Alam, as well as the selling price of dried lomek products using the cost plus pricing method. This study uses a quantitative descriptive research method by collecting data from BUMDes Kuala Alam, observing the data and displaying the results in the tables described. This study obtained the results that there are differences in determining the selling price of dried lomek between the methods used by BUMDes and the Cost Plus Pricing method. The difference in the inclusion of variable factory overhead costs and fixed factory overhead costs. The method of determining the selling price of Cost Plus Pricing is able to determine the selling price that is able to compete. Because the selling price is below the market selling price range for 100 Kg is Rp. 13,700/pcs and the selling price of 1000 Kg is Rp. 8,000/pcs. Keywords: Pricing Strategy, Selling Price, Cost Plus Pricing Method.